1996
DOI: 10.1177/1073191196003003007
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Differences in School Age Children after Perinatal Stroke

Abstract: Little is known about the influence of the right hemisphere (RH) on social and emotional development in children. In order to examine the effect of RH damage on behavioral function, the Personality Inventory for Children was administered to parents of 17 children who had suffered perinatal strokes and 23 control children. Children with focal brain lesions, regardless of hemisphere, had higher T scores (indicating greater abnormality) than controls on scales measuring social competence, emotional behavior, cogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Past studies that have examined the effect of childhood stroke on a single cognitive domain (e.g., IQ: Ballantyne et al, 1994;Goodman & Yude, 1996;Hogan et al, 2000), language skills (Bates & Roe, 2001;Bates et al, 1997bBates et al, , 1999bReilly et al, 1998), visuospatial skills (Akshoomoff et al, 2002;Schatz et al, 2000;Stiles, 2000b), and behavioral profiles (Goodman & Yude, 1997;Max et al, 2002aMax et al, , 2002bTrauner et al, 1996Trauner et al, , 2001. The strength of the current study lies in its breadth.…”
Section: Discussionmentioning
confidence: 81%
“…Past studies that have examined the effect of childhood stroke on a single cognitive domain (e.g., IQ: Ballantyne et al, 1994;Goodman & Yude, 1996;Hogan et al, 2000), language skills (Bates & Roe, 2001;Bates et al, 1997bBates et al, , 1999bReilly et al, 1998), visuospatial skills (Akshoomoff et al, 2002;Schatz et al, 2000;Stiles, 2000b), and behavioral profiles (Goodman & Yude, 1997;Max et al, 2002aMax et al, , 2002bTrauner et al, 1996Trauner et al, , 2001. The strength of the current study lies in its breadth.…”
Section: Discussionmentioning
confidence: 81%
“…Whereas earlier studies suggested a negative impact of neonatal stroke on emotional expression, comprehension and social skills (Reilly et al. , 1995; Goodman and Graham, 1996; Goodman and Yude, 1996; Trauner et al. , 1996a,b; Goodman, 1998), Trauner et al.…”
Section: Behavioral Outcomementioning
confidence: 82%
“…However, current evidence suggests that age at stroke onset is unrelated to social outcomes (Hurvitz et al, 2004). Rather, the risk of social deficits appears to be elevated following stroke at any age during childhood (Anderson et al, , 2009Greenham, SpencerSmith, Anderson, Coleman, & Anderson, 2010;Trauner et al, 1996). Little is known regarding the impact of focal brain insult on social competence and, of interest, studies attempting to identify brain-behavior links for other cognitive and functional outcomes following pediatric stroke have been disappointing (Ganesan, Ng, Chong, Kirkham, & Connelly, 1999;Westmacott, Askalan, Macgregor, Anderson, & Deveber, 2010).…”
Section: Brain Correlates Of Social Competencementioning
confidence: 97%
“…Little is known regarding the impact of focal brain insult on social competence and, of interest, studies attempting to identify brain-behavior links for other cognitive and functional outcomes following pediatric stroke have been disappointing (Ganesan, Ng, Chong, Kirkham, & Connelly, 1999;Westmacott, Askalan, Macgregor, Anderson, & Deveber, 2010). Trauner et al (1996) describe elevated risk of social impairment with pediatric stroke involving extra-frontal structures, while report that children with stroke involving subcortical brain regions may be vulnerable, particularly with respect to emotional regulation. Studies conducted by Max et al (2002Max et al ( , 2010 also link lesion location, particularly frontal pathology, to elevated risk of attention deficit 472 ANDERSON ET AL.…”
Section: Brain Correlates Of Social Competencementioning
confidence: 98%
See 1 more Smart Citation